An investigation of solar cell interconnection schemes within CPV modules using a validated temperature‐dependent SPICE network model. (25th October 2012) - Steiner, Marc; Siefer, Gerald; Bett, Andreas W.
ABSTRACT In this paper, we present a temperature‐dependent network model of a concentrator photovoltaic (CPV) module. The ability of this network model to calculate different interconnection schemes within CPV modules is validated, and there is good agreement between the measured and calculated data. The model is used to quantify the influence of an inhomogeneous current and of a temperature distribution between the solar cells on the power output of a module. The different interconnection schemes that combine parallel and series connections are compared. The optimal interconnection scheme strongly depends on the variations in the short current densities and temperature differences between the solar cells as well as on the risk of 'sudden death' of individual solar cells. Optimal interconnection schemes for several scenarios are developed. A combination of parallel and series interconnections is found to be the most robust interconnection. Copyright © 2012 John Wiley & Sons, Ltd.